ENSURING BANKING LIQUIDITY IN THE CURRENT CONDITIONS - HARKUSHA, Yuliya; ANTONIUK Аnastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the theoretical and methodological foundations of ensuring bank liquidity. The essence of the concepts "bank liquidity" and "banking system liquidity" has been defined. External and internal factors influencing the state of bank liquidity are indicated. In the study, an analysis of domestic banks’ compliance with liquidity standards established by the National Bank of Ukraine was carried out. The state of bank liquidity was determined in accordance with the coefficient of the liquid ratio of loans granted to deposits attracted by the banking system. The share of securities in the structure of assets of domestic banks and separately the share of state securities were determined. It was determined that the reasons for the tendency to decrease the specific weight of loans in the structure of banks’ assets can be called the following: the general economic and political situation in the country does not favor active lending, especially during martial law, because the risks of non-repayment of loans increase significantly; the need to increase own capital and improve its structure, which are the requirements of the National Bank of Ukraine; peculiarities of the monetary policy of the National Regulator in the conditions of the inflation targeting regime, keeping the discount rate indicator at a fairly high level for quite a long period and using certificates of deposit as a permanent monetary instrument. Conclusions were made and proposals were made to improve the process of ensuring the liquidity of the banking system of Ukraine, including: harmonization of fiscal and monetary policy aimed at restoring economic activity; activation of bank lending by providing guarantees to the Cabinet of Ministers of Ukraine, especially to important industries; lowering the level of the key rate, taking into account the low level of consumer inflation and the factors of inflationary processes, which are mainly non-monetary.